Dead or alive - Clancy, Tom, 1947-; Blackwood, Grant (New York : G.P. Putnam's Sons, 2010)
Jack Ryan, Jr. and his Campus colleagues John Clark and Ding Chavez, go after a vicious terrorist mastermind--the Emir--and they will bring him in ... dead or alive.
Keywords: Terrorists -- Fiction; Terrorism -- Prevention -- Fiction; Fathers and sons -- Fiction; Intelligence officers -- Fiction; Children of presidents -- Fiction; Terrorism -- Prevention -- Fiction; Ryan, Jack (Fictitious character) -- Fiction; Undercover operations -- Fiction; Suspense fiction